Mechanical and thermal properties of carboxymethyl fibers (CMF)/PVA based nanocomposite membranes - Niazi, M.B.K. (Korean Society of Industrial Engineering Chemistry, 2020)
Carboxymethyl fibers (CMF) of cellulose are renewable biopolymer and have shown strong reinforcing properties when added to a compatible polymer matrix. The objective of this study was to investigate the effect of CMF on the mechanical, thermal and swelling properties of polyvinyl alcohol (PVA) membranes. The PVA/CMF composite membranes with different proportions of CMF ranging from 1 wt. to 6 wt. were prepared by solution casting method. The membranes were characterized by SEM, TGA, XRD, FTIR and mechanical testing. The results revealed that at low CMF concentration composite membranes showed homogenous dispersion of CMF in PVA matrix. The incorporation of CMF enhanced the crystallinity of composite membranes with increase in relative humidity (RH). Furthermore, the mechanical strength and moisture uptake of PVA/CMF nanocomposite membranes were enhanced after inclusion of CMF. TGA and DSC results revealed that the addition of CMF has no significant impact on the thermal properties. PVA/CMF nanocomposite membranes showed good potential to be applied for gas separation application particularly for CO2 capture. Â© 2020 The Korean Society of Industrial and Engineering Chemistry